2011
DOI: 10.1111/j.1365-2648.2011.05769.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing in general practice: organizational possibilities for decision latitude, created skill, social support and identity derived from role

Abstract: Collegial and supervisory support in the work environment predicts organizational possibilities for practice nurse decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
4
15
0
2
Order By: Relevance
“…These findings resonate with the findings of other UK and international studies into the role, function and educational needs of practice nurses (Crossman, Pfeil, Moore, & Howe, 2015;Queens Nursing Institute, 2016;Merrick et al, 2012). The generalist nature of practice nursing has given rise to a role that is undifferentiated in scope and isolated from the wider health and social care network with whom the patients interact.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…These findings resonate with the findings of other UK and international studies into the role, function and educational needs of practice nurses (Crossman, Pfeil, Moore, & Howe, 2015;Queens Nursing Institute, 2016;Merrick et al, 2012). The generalist nature of practice nursing has given rise to a role that is undifferentiated in scope and isolated from the wider health and social care network with whom the patients interact.…”
Section: Resultssupporting
confidence: 75%
“…They identify among other factors, the rise of evidence-based medicine and the establishment of the National Institute for Health and Clinical Excellence (NICE); new public management with an emphasis on monitoring and control and increased concerns about variation in practice in primary care giving rise to variation in patient outcomes. Similar processes to the QOF are reported in Europe (Szecsenyi et al, 2011) and Australia (Merrick et al, 2012) although they are not as detailed and extensive as those introduced in the UK.…”
Section: Introductionsupporting
confidence: 56%
“…Merrick et al . () found that 44.4% of New South Wales PNs who responded to a survey held a hospital certificate as their highest educational qualification. Education for PNs often occurs through short courses addressing the specific tasks covered by MBS rebates rather than through postgraduate qualifications (Halcomb et al .…”
Section: Resultsmentioning
confidence: 99%
“…This study also revealed that CBL could improve critical thinking ability of students, suggesting that CBL-method in combined with casedirected study significantly improved core competency of nursing undergraduates in solving clinical problems, and made them more competent for clinical practice in future [5].…”
Section: Application Of Case-based Learning In Instructing Clinical Smentioning
confidence: 86%
“…Clinical practice is therefore one indispensable stage for nursing students transiting from class-based learning towards clinical practice. Teaching of nursing skills is the core syllabus of clinical intern [4,5]. However, the teaching of clinical skills still mainly depends on the teacher demonstration, followed by practice under supervision and evaluation, and largely ignoring cultivation of comprehensive analysis, communication, response and critical thinking features of students [6].…”
Section: Introductionmentioning
confidence: 99%